Synbiotic therapy (Bifidobacterium longum/Synergy 1) initiates resolution of inflammation in patients with active ulcerative colitis: a randomised controlled pilot trial. (11th January 2005) - Furrie, E; Macfarlane, S; Kennedy, A; Cummings, J H; Walsh, S V; O'Neil, D A; Macfarlane, G T
Abstract : Background and aims: Ulcerative colitis (UC) is an acute and chronic inflammatory disease of the large bowel with unknown aetiology. The immune response against normal commensal microorganisms is believed to drive inflammatory processes associated with UC. Therefore, modulation of bacterial communities on the gut mucosa, through the use of probiotics and prebiotics, may be used to modify the disease state. Methods: A synbiotic was developed for use in UC patients combining a probiotic, Bifidobacterium longum, isolated from healthy rectal epithelium, and a prebiotic (Synergy 1), a preferential inulin-oligofructose growth substrate for the probiotic strain. Treatment was employed in a double blinded randomised controlled trial using 18 patients with active UC for a period of one month. Clinical status was scored and rectal biopsies were collected before and after treatment, and transcription levels of epithelium related immune markers were measured. Results: Sigmoidoscopy scores (scale 0–6) were reduced in the test group (start 4.5 (1.4), end 3.1 (2.5)) compared with placebo (start 2.6 (2.1), end 3.2 (2.2)) (p = 0.06). mRNA levels for human beta defensins 2, 3, and 4, which are strongly upregulated in active UC, were significantly reduced in the test group after treatment (p = 0.016, 0.038, and 0.008, respectively). Tumour necrosis factor α and interleukin 1α, which are inflammatory cytokines that drive inflammation and induce defensin expression, were also significantly reduced after treatment (p = 0.018 and 0.023, respectively). Biopsies in the test group had reduced inflammation and regeneration of epithelial tissue. Conclusions: Short term synbiotic treatment of active UC resulted in improvement of the full clinical appearance of chronic inflammation in patients receiving this therapy.